Pengaruh Sistem Pelaporan dan Kejelasan Sasaran Anggaran Terhadap Akuntanbilitas Kinerja Instansi Pemerintah (Studi Pada Satuan Kerja Pemerintah Aceh) - AR, Mulyadi; Syamsidar, Syamsidar; Efendy, Dedy (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2018)
This research aims to determine the effect of the reporting system and the clarity of the budget target on the accountability of the performance of Aceh Government Agencies, the formulation of the problem in this study is whether there is an effect on the reporting system and clarity of budget targets on the accountability of Aceh Government performance both simultaneously and partially.Data collection uses a questionnaire, and is analyzed qualitatively and converted into quantitative data using a Likert Scale. Data analysts to see the effect of dependent variables with independent variables using analysis of multiple linear regression equations.The population of this study amounted to 84 respondents, who were examined by the Head of Section (Head of Section) and Head of Division (Head) in Aceh Government Agencies. The results of the study found that the reporting system and the clarity of budget targets simultaneously had a significant effect on the performance of the Aceh Government. The partial reporting system has a significant effect on the accountability of the performance of Aceh Government Agencies. Clarity of budget targets partially has a significant effect on the accountability of the performance of Aceh Government Agencies. The reporting system has more dominant influence on the accountability of the performance of Aceh Government Agencies. It is expected that in the future the Aceh Government will pay more attention to the clarity of the budget goals in budgeting, because the results of the research regression coefficients have the smallest effect on the accountability of the performance of Aceh Government agencies in clarity of budget targets, with the hope that these variables will have greater influence on the accountability of Agency performance The Aceh Government in the future.